Utilization of glycerol solution for hydrogen production by a combination of photocatalysis and electrolysis processes with Fe-TiO2 nanotubes - Santoso, Calvin; Ratnawati; Slamet (Communications in Science and Technology, 2023)
A combination of photocatalysis and electrolysis (photoelectrocatalysis) for the simultaneous degradation of glycerol and hydrogen production using Fe-TiO2 nanotubes has been studied. This photocatalyst was synthesized through Ti anodization followed by Fe deposition with Fe(NO3)3 as precursor using the SILAR (successive ionic layer adsorption and reaction) method. The effects of Fe loading (based on the number of SILAR cycles) on TiO2 nanotubes and glycerol concentration were examined. The generated TiO2 nanotubes were 100% anatase phase with crystallite size between 25 and 29 nm. The results of UV-Vis DRS showed that the number of SILAR cycles of Fe dopant determined the magnitude of the decrease in the band gap of photocatalysts up to 2.74 eV, notably lower than a typical value of 3.15 eV associated with TiO2 anatase. FESEM/EDX, TEM, and HRTEM characterizations indicated the formation of neatly arranged TiO2 nanotubes with Fe deposited on the surface. The photoelectrocatalytic process increased the hydrogen produced by up to 5 times compared to a single photocatalytic or electrolysis process. The photocatalyst sample with Fe deposited on TiO2 nanotubes via a SILAR method with 15 cycles outperformed its bare TiO2 nanotube counterpart by producing hydrogen by 2.5 times (405.8 mmol/m2). Glycerol photo-reforming at 10% concentration produced hydrogen 6 times greater than water splitting (0% glycerol).